An Assessment Of The Provision Of Recreational Facilities In The Greater-Jos, Plateau State, Nigeria - Wash, Peter Musa (2021)
The spatial provision of recreational facilities is highly critical, being the vital services that affect the wellbeing of residents and community development. The provision is an activity that demands a conscience-led approach; hence overcoming daunting problems of setback in implementing policies, inaccessibility, inappropriate provision of the facility and stakeholders’ performance. Therefore, this study is aimed at assessing the provision of recreational facilities in the Greater-Jos. Greater-Jos comprises of two and parts of other four Local Government Areas, in Plateau State, North Central of Nigeria with population estimated at 1.5 million. The effectiveness of policy implementation is determined based on the aspects of accessibility, appropriateness, and performance of stakeholders in the provision of recreational facilities. Multi-method research was adopted where Geographic Information System (GIS), questionnaire survey and interviews were conducted. The data were analysed by using ArcGIS, partial least squares structural equation modelling (WarpPLS) and Atlas.ti8, respectively. By triangulation, the results revealed that the provision of recreational facilities positively affects the relationship between appropriateness and stakeholders’ involvement. In contrast, the provision of recreational facilities negatively affects the relationship with regards to accessibility indicators. The findings further show the spatial distribution of the recreational facilities, which are unequally spread within the ten sectors of the Greater Jos. Relating the results to the policy proposed in the Greater Jos Master Plan produced in 2009, the findings are astonishingly conflicting.